Licensing virus-specific T cells to secrete the neutrophil attracting chemokine CXCL-8 during hepatitis B virus infection. - Adam J Gehring; Sarene Koh; Adeline Chia; Komathi Paramasivam; Valerie Suk Peng Chew; Zi Zong Ho; Kang Hoe Lee; Mala K Maini; Krishnakumar Madhavan; Seng Gee Lim; Antonio Bertoletti (PLoS ONE)
T cell functional plasticity helps tailor antiviral immunity during different phases of infections. We tested whether, during different phases of HBV infection, virus-specific T cells can acquire specific proinflammatory functions that could drive granulocyte/mononuclear cell liver infiltration. Multifunctional analysis of HBV-specific T cells during acute and chronic HBV infection revealed that HBV-specific T cells had the capacity to produce the neutrophil chemokine CXCL-8 but not IL-17. CXCL-8 producing T cells were detectable in the liver of chronic HBV patients with active hepatitis; while in acute HBV patients CXCL-8 production by T cells was temporally limited to the acute phase of disease, concomitant with the peak of liver inflammation. Characterization of the conditions necessary for the development of CXCL-8 producing T cells showed a requirement for IL-7 and IL-15 during T cell expansion. These data show that functional plasticity of virus-specific T cells spontaneously occurs during HBV infection and that an environment rich IL-7 and IL-15 can license T cells with the ability to produce CXCL-8 and potentially influence liver pathology.